English for Political Sciences: The Need Analysis Based Course Design - Maolana Tepuri; Rosyidah, Naeli; Nur Tsani, M. Happy (Tarling : Journal of Language Education, 2024)
This research aims to find out the needs and to design a course for the political sciences based on need analysis. To achieve this goal, a need analysis approach was employed with survey and interview to the social and political science students of Hasanuddin University and the professionals of political sector in the Banyumas Regional Government. The data collected were analysed using language-centred course design approach. The study highlights the specific language skills and communication needs in politics. It provides insights for designing a tailored ESP course by recommending relevant materials, authentic political texts, and interactive activities to enhance language proficiency and political literacy. The implications of this research are significant for English language educators, curriculum designers, and policymakers in the field of political education. By addressing the specific needs of students and providing them with appropriate language support, this study is beneficial to contribute to the academic and professional success of students in the political sector with English. Keywords: ESP; Politics; Need Analysis; Course Design